Concerted Albeit Not Pericyclic Cycloadditions: Understanding the Mechanism of the (4+3) Cycloaddition between Nitrones and 1, 2‐Diaza‐1, 3‐dienes. Issue 2 (8th August 2018) - Pedrón, Manuel; Delso, Ignacio; Tejero, Tomás; Merino, Pedro
Abstract : The mechanism of (4+3) cycloaddition reactions of nitrones with 1, 2‐diaza‐1, 3‐dienes has been studied by using density functional theory (DFT) methods. The cycloaddition reaction takes place through an asynchronous concerted transition state that reflects a two‐stage process in which the formation of the first bond occurs close to the transition state, while the second bond forms well after the transition state. The alternative stepwise mechanism is higher in energy than the concerted process. In this mechanism, the nitrone oxygen acts as a nucleophile by attacking the more electrophilic terminal carbon of the 1, 2‐diaza‐1, 3‐diene to form an intermediate. The second step of the reaction is the rate‐limiting one, which is higher in energy than that observed for the concerted process. Topological analysis of the gradient field of electron localization function (ELF) provides a complete characterization of the electron density changes during the course of the reaction. Abstract : The (4+3) cycloaddition reaction of nitrones with 1, 2‐diaza‐1, 3‐dienes takes place through a highly asynchronous concerted process in which the formation of the two new bonds takes place consecutively after the transition state. The potential energy surface shows a bifurcation between two different transition states corresponding to concerted and stepwise mechanisms the former being preferred